Institutionalist versus distortionist views of labor market reforms: An investigation into the post-liberalized manufacturing sector in India - Anup Kumar Bhandari; Arun Sudarsan (Journal of Economics, Finance and Administrative Science, 2016)
Labor regulation and employment relation has been investigated in India in light of the seminal work of Besley and Burgess (2004), considering formal sector manufacturing employment as the explained variable. Empirical findings support, although not very strongly, the institutionalist view, i.e., pro-worker amendment in labour laws induces employment. Among the other factors, real wage rate has significant negative effect on employment, whereas that for real per capita developmental capital expenditure, per capita electricity generation capacity and real per capita net state domestic product is significant positive. However, effect of per capita real developmental revenue expenditure is inconclusive. In other words, although it improves employability of workers through their human capital improvement, which is probably met up at the cost of worsening overall infrastructural development, through reducing corresponding capital expenditure! Supporting evidence has also been provided favoring this conjecture. – – La normativa y la regulación laboral se han investigado en la India a raíz del trabajo original de Besley y Burguess (2004), tomando como variable el empleo formal en el sector manufacturero. Los hallazgos empíricos respaldan, aunque no rotundamente, la visión institucionalista, es decir, que la enmienda a favor del trabajador en la legislación laboral fomenta el empleo. Entre otros factores, la tasa de salario real tiene un impacto significativamente negativo en el empleo, mientras que para la inversión de capital de desarrollo per cápita, la capacidad de generación de electricidad per cápita y el producto interno es significativamente positiva. No obstante, el efecto del costo de los ingresos del desarrollo real per cápita no es concluyente. En otras palabras, si bien esto favorezca la inserción laboral de los trabajadores con una mejora del capital humano, probablemente se consiga a costa de empeorar el desarrollo de infraestructura al reducir la inversión en capital correspondiente. Se presenta evidencia que avala esta conjetura.
Keywords: J52; K31; O14; 330; Labor regulation; Formal sector; Manufacturing employment; Liberalization; Regulación laboral; Sector formal; Empleo manufacturero; Liberalización